Treasures of America's national parks. 2, Yellowstone [videorecording (DVD)]. (Distributed by Questar, 2008)
Llama trekking, wolf watching and geyser gazing are just a few of the out-of-the-ordinary activities that await. Inside Grand Teton National Park, saddle up for a working dude ranch, feel the rush of whitewater rafting and more.